PRODUKSI HIJAUAN DAN KAPASITAS TAMPUNG TERNAK DI RAWA KECAMATAN MENGGALA KABUPATEN TULANG BAWANG - Hanan Rilo Pangestu, Liman, Agung Kusuma Wijaya, and Muhtarudin (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
This study aimed to determine forage production and carrying capacity in the swamp Menggala District, Tulang Bawang Regency, Lampung Province. This research was conducted in August - October 2017 at the swamp, Menggala District, Tulang Bawang Regency, Lampung Province and the Laboratory of Nutrients and Feed technology Department of Animal Husbandry, Faculty of Agriculture, Lampung University. This study used survey method, with sampling taken using purposive sampling. The data used from this study consisted of primary and secondary data. The results showed that forage production in the district of Menggala in a year produced as much as 83.839.260 kg / year and 14.792.992 kg / year in dry matter. based ofn forage production as much as 14.792.992 kg / year can accommodate 4503 AU / year. Key word: Carrying capacity, Forage, Production, Swamp